THE EFFECT OF HERB AND YEAST ADDITION ON THE ORGAN PROFILE AND DIGESTIVE TRACT OF BROILER CHICKENS - Yuliani, Ni Sri; Sakan, Gerson Y. I.; Suryatni, Ni Putu F. (Buletin Veteriner Udayana, 2022)
This study aimed to examine the effect of herbs and yeast addition to drinking water on the weight and length of the digestive tract of broiler chickens. The study design used a completely randomized design with four treatmens and five repetitions. Group P1: Herbal medicene 10 ml/Liter drinking water, P2: Herbal medicine 10 ml added with yeast 1 g/Liter drinking water, P3: Yeast 1g/Liter drinking water, PO: Controls given water. Data analysis used analysis of variance (Anova) and if the result had a significant effect, it was continued with Duncan's Multiple Distance tes. The addition of herbs and yeast to drinking water had an effect on the size of the spleen and pancreas and significantly (P<0,05) on the weight of the spleen and pancreas, but had no effect (P> 0,05) on the weight and length of the small intestine, liver and broiler final weight. The addition of herbs and yeast to drinking water can reduce the weight of the small intestine and shorten the intestine, increase the weight of the spleen and pancreas, but have the same effect on the final weight. The use of herbal medicene should be fermented together with yeast to determine its effectiveness in the digestive tract.